HUBUNGAN ANTARA SELF-COMPASSION DENGAN SELF-CRITICISM PADA DEWASA AWAL YANG TERPAPAR KONTEN PRESTASI DI MEDIA SOSIAL - Maryam Zahra; Raja Oloan Tumanggor (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid growth of social media in the digital era has led emerging adults to be increasingly exposed to achievement-oriented content, including academic accomplishments, career success, and personal achievements. Such exposure frequently elicits upward social comparison, which may, in turn, intensify tendencies toward self-criticism. However, self-compassion is widely regarded as a protective factor that can mitigate these negative effects. Therefore, this study aimed to examine the relationship between self-compassion and self-criticism among emerging adults who are exposed to achievement-related content on social media. The participants consisted of 189 individuals aged 18–29 years who actively use social media and have previously encountered achievement-related content. Data were collected online using the Self-Compassion Scale (SCS) and the Forms of Self-Criticizing/Attacking and Self-Reassuring Scale (FSCRS). Subsequently, data analysis was conducted using Spearman’s correlation. The results revealed a strong and significant negative relationship between self-compassion and self-criticism (ρ = –0.600, p < .001). In other words, higher levels of self-compassion were associated with lower tendencies toward self-criticism. Overall, these findings underscore the crucial role of self-compassion as an important protective factor against the negative psychological impacts of exposure to achievement-related content on social media. Accordingly, this study is expected to serve as a foundation for the development of interventions aimed at enhancing self-compassion in order to strengthen the mental health of emerging adults in the digital era.